2021
DOI: 10.15408/ijee.v1i1.20681
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Learners’ Self-directed Learning and Resilience in Online English Classes: Assessing Interaction with L2 Achievement

Abstract: The present study was conducted to find the relationship between English for Academic Purposes (EAP) learners’ Self-directed Learning (SDL) and their achievement as measured with their EAP class grades as well as the relationship between these grades and their resilience. This study used a survey as the method of data collection and 157 learners who were enrolled in EAP online classes willingly participated in the study. Results of Pearson’s correlation and Regression analysis showed that learners’ SDL was ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The four principles for teaching vocabulary are as follows; the first is to focus on the most useful language. First, the second is to focus on the vocabulary correctly, the third is to pay attention to high-frequency words, and the last is to encourage students to reflect and be responsible for learning (Hakim, 2019;Subekti, 2021). Previous research has shown that YouTube is important in learning English (Bunna et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The four principles for teaching vocabulary are as follows; the first is to focus on the most useful language. First, the second is to focus on the vocabulary correctly, the third is to pay attention to high-frequency words, and the last is to encourage students to reflect and be responsible for learning (Hakim, 2019;Subekti, 2021). Previous research has shown that YouTube is important in learning English (Bunna et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The present study employed online interviews as the only method of data collection. The present study was the continuation of two quantitative studies involving learners of English for Academic Purposes (EAP) classes, a branch of ESP, at a university in Java, Indonesia in a survey investigating the relationship between their SDL and resilience (Subekti, 2021a) and the relationship between these two constructs and L2 achievement (Subekti, 2021b). The EAP classes were offered in the first semester of the 2020/2021 academic year.…”
Section: Methods Research Design and Participantsmentioning
confidence: 99%
“…The present study involved six selected participants of these two previous studies. The selection was based on whether these participants indicated their willingness to be inter-viewed when filling out the questionnaires in the earlier study (Subekti, 2021a(Subekti, , 2021b and their SDL levels as measured through their responses in the SDL questionnaires. Three participants with the highest SDL and three participants with the lowest SDL were selected for the present study.…”
Section: Methods Research Design and Participantsmentioning
confidence: 99%